RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF ATORVASTATIN AND EZETIMIBE IN PHARMACEUTICAL DOSAGE FORM - Raul, Saroj Kumar; Aravelli, Ratna Bhaskar; Jhansi, Durgasi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The aim was to develop a simple, selective, linear, precise, and accurate reverse phase high performance liquid chromatography method for simultaneous estimation of atorvastatin and ezetimibe in tablet dosage form. Methods: The chromatographic separation was performed using hypersil BDS C18 coloumn (250 mm Ã— 4.6 mm, 5 mm particle size). Mobile phase composed of phosphate buffer pH-4.5 and acetonitrile (35:65 v/v) at a flow rate of 1 ml/min. Detection was carried out using photodiode array detector at 228 nm. The method was validated as per ICH guidelines. Results: The retention time for atorvastatin and ezetimibe are observed as 2.36 and 3.43 minutes respectively. Linearity range was observed in concentration of 12.5-75 Î¼g/ml for both atorvastatin and ezetimibe. The percentage recoveries of atorvastatin and ezetimibe are 100.21% and 100.22% respectively. The correlation coefficients for both the components are close to 1. Conclusion: This method is simple, selective, linear, precise, accurate and sensitive hence can be successfully employed for the routine quality control of dosage forms containing both the drugs in pharmaceutical industries. Keywords: Reverse transcription polymerase chain reaction, Method development, Atorvastatin, Ezetimibe, Validation.